Population Genetic of Kawakawa (Euthynnus affinis) in Sumatera Island - Zedta, Raymon Rahmanov; Maduppa, Hawis H; Zamani, Neviaty Putri; Subhan, Beginer; Sani, Lalu Mukhsin Iqbal (Universitas Gadjah Mada, 2024)
Over the past five decades, there has been a growing trend in the capture of kawakawa (Euthynnus affinis), which, alongside its potential to support small-scale commercial fisheries, highlights its significance.However, there is inadequate data on this species for suitable management and conservation status. This study aimed to investigate the genetic diversity, population structure, and connectivity of the kawakawa in the three major fishing port in Sumatra, namely Belawan , Padang, and Lampung by using DNA mitochondria control region (d-loop) Sequence. In total, 78 sequences of kawakawa with an average size of 303 bp, we found 36 polymorphic sites and 56 haplotypes from all population were identified with DNA compatibility values of 97-100%. We found the genetic diversity values in Sumatera Island were high (h = 0.950; π = 0.034), with the highest genetic diversities value in Padang (h = 0.990; π = 0.082) and the lowest in Belawan (h = 0.929; π = 0.082). AMOVA and Fst analyses revealed no differentiation in each population (Fst = 0.005). The haplotype distribution and connectivity analyses showed genetic mixing among the three populations. This study showed a single stock at the study sites and suggests management measures at a regional level to maintain the population.